THE EVALUATION OF ANTIHYPERTENSIVE EFFICACY OF ORALLY-DISPERSING FORM OF PERINDOPRIL IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION - R. A. Khokhlov; E. E. Tsareva; V. I. Taranina (Российский кардиологический журнал, 2014)
Aim. To evaluate the influence of Prestarium A (perindopril as orally dispersing pills, “Les Laboratories Servier”, France) on dynamics of systolic and diastolic arterial pressure and life quality parameters in patients with mild to moderate arterial hypertension.Material and methods. A 12-week prospective observation was performed on 13 women and 9 men in the age of 38 to 60 (mean age 49 y. o.) with mild and moderate arterial hypertension, who received Prestarium A as antihypertensive treatment with the mean daily dose 8,4±2,3 mg. The main endpoints were: 1) changes in mean office blood pressure and of the life quality by EQ-5Q and SF-36 questionnaires at the final visit; 2) intolerability of the drug.Results. In 12 weeks of Prestarium A therapy mean blood pressure significantly decreased from baseline 159,6±12,3 и 101,2±4,3 mmHg to 133,7±7,8 и 83,5±6,2 mmHg (р=0,0009 и р=0,0011, resp., for systolic and diastolic blood pressure; Wilkokson criteria). Target blood pressure (<140 and 90 mmHg) was achieved in 4 weeks in 13 (59%), in 8 weeks in 17 (77%), and in 12 weeks in 20 (86%) patients, and there were no any side effects. Monotherapy by Prestarium A was followed by significant improvement of life quality of the patients according to analogue scale (EQ-5D) from 60,3±6,8 to 75,4±7,3 points (р=0,0041; Wilkockson criteria) and by the scale of physical functioning SF-36 from 48,6±7,6 to 61,6±5,8 points (р=0,0001; Wilkokson criteria).Conclusion. Therapy with Prestarium A in patients with non-complicated mild and moderate arterial hypertension during 12 weeks with average dosage 8,4±2,3 mg made it to achieve target blood pressure levels in 86% patients. Relevant decrease of arterial pressure, achieved by the last visit, was followed by an improvement of lfe quality of the patients, and the therapy itself was perfectly tolerated.